2014
DOI: 10.1038/mp.2014.158
|View full text |Cite
|
Sign up to set email alerts
|

Common polygenic variation and risk for childhood-onset schizophrenia

Abstract: Childhood-onset schizophrenia (COS) is a rare and severe form of the disorder, with more striking abnormalities with respect to prepsychotic developmental disorders and abnormities in the brain development compared with later-onset schizophrenia. We previously documented that COS patients, compared with their healthy siblings and with adult-onset patients (AOS), carry significantly more rare chromosomal copy number variations, spanning large genomic regions (4100 kb) (Ahn et al. 2014). Here, we interrogated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…For example, the top four prioritized coding target genes ( NTRK2 , RELN , HDAC1 , and KIF5C ) have been previously associated with cognitive disorders or psychiatric illness, including SCZD [Sharma et al., ; Otnaess et al., ; Ovadia and Shifman, ; Bergen et al., ]. As a whole, we identified an enrichment of SCZD candidate genes in P1 compared with P2, which is in line with recent studies on SCZD, showing that affected individuals have increased burden of genetic variants [Ahn et al., ; Chan, et al. ; Kong et al., ].…”
Section: Discussionsupporting
confidence: 89%
“…For example, the top four prioritized coding target genes ( NTRK2 , RELN , HDAC1 , and KIF5C ) have been previously associated with cognitive disorders or psychiatric illness, including SCZD [Sharma et al., ; Otnaess et al., ; Ovadia and Shifman, ; Bergen et al., ]. As a whole, we identified an enrichment of SCZD candidate genes in P1 compared with P2, which is in line with recent studies on SCZD, showing that affected individuals have increased burden of genetic variants [Ahn et al., ; Chan, et al. ; Kong et al., ].…”
Section: Discussionsupporting
confidence: 89%
“…This approach holds incredible promise for aiding in the categorizing of specific phenotypic or risk subgroups, for example, among those with PGS in upper and lower quantiles. Recently these methods have been applied to identify individuals at high risk for early disease onset 34, 35 , those likely to suffer from comorbid disorders 36, 37 , those with treatment resistant disease 38 , those likely to benefit from intervention 39 and those who are more likely to suffer from more severe chronic disease 40 . PGS methods will continue to be actively used in research settings to identify phenotypically interesting or unique case subsets.…”
Section: Conclusion – Future Directionsmentioning
confidence: 99%
“…Another study tried to identify brain regions whose function may be related to BD PRS and also examined the discrimination by the BD PRS of BD patients from unaffected first‐degree relative and unrelated healthy controls (Dima, de Jong, Breen, & Frangou, ), but the group sizes were small. A study of Ahn, An, Shugart, and Rapoport () also found that childhood‐onset SZ patients had higher genetic risk scores for SZ than their healthy siblings with a SZ PRS defined from the PGC results.…”
Section: Introductionmentioning
confidence: 95%